2009
DOI: 10.1063/1.3213370
|View full text |Cite
|
Sign up to set email alerts
|

Raman studies of GaN/sapphire thin film heterostructures

Abstract: Using Raman spectroscopy, we have studied the optical phonon modes of GaN nucleation layers with the thicknesses of 7 and 45nm, grown on sapphire (0001) substrates by metal organic chemical vapor deposition at low temperatures (500–600°C). These layers consisted of mixed hexagonal and cubic phases. The Raman results from mixed phases were compared with those from pure hexagonal layers which were grown at higher temperatures over 1000°C. The E2H and A1(LO) phonon modes are observed at 548 and 733cm−1 for 45nm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…36 In regular GaN/sapphire epitaxial growth, the presence of in-plane tensile strain is normally observed. 37 Moreover, the effect of the Ga 2 O 3 interlayer on the overall stress of the grown wafer can be considered insignificant since the PL peak wavelengths of GaN/sapphire and GaN/Ga 2 O 3 /sapphire fabricated under N 2 environment were identical at 368 nm, as shown in Fig. 6b.…”
Section: Resultsmentioning
confidence: 98%
“…36 In regular GaN/sapphire epitaxial growth, the presence of in-plane tensile strain is normally observed. 37 Moreover, the effect of the Ga 2 O 3 interlayer on the overall stress of the grown wafer can be considered insignificant since the PL peak wavelengths of GaN/sapphire and GaN/Ga 2 O 3 /sapphire fabricated under N 2 environment were identical at 368 nm, as shown in Fig. 6b.…”
Section: Resultsmentioning
confidence: 98%
“…Complicating the issue, this same region is usually at the junction of low coefficient of thermal expansion (CTE) SiN x , high coefficient gold (Au) gate metal, and middle valued III-N semiconductor. In addition, residual stresses exist due to fabrication processes [6,[12][13][14][15]. SiN x passivation, in particular, can be deposited in a highly stressed state [16,17] and the AlGaN layer has large amounts of intrinsic tensile stress on the order of 1-3 GPa [6,12] from pseudomorphic growth on GaN.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great importance to understand and control the occurrence of these crystalline structures. Previous works have demonstrated that, in not-intentionally doped (NID) GaN layers, an obvious lower substrate temperature is necessary to obtain a pure cubic phase rather than that of a pure hexagonal phase by metal organic chemical vapor deposition (MOCVD) or molecular-beam epitaxy (MBE) [8,[11][12][13]. Recently, uniformly distributed c-GaN and h-GaN subgrains have been simultaneously found in NID GaN nucleation layers grown on sapphire substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, uniformly distributed c-GaN and h-GaN subgrains have been simultaneously found in NID GaN nucleation layers grown on sapphire substrate. Both subgrains provide templates for the subsequent epitaxial growth, having important influence on the crystalline quality of GaN [9,12,14]. However, few studies have examined the possible mixed crystalline structures in doped AlGaN alloys with high aluminum content.…”
Section: Introductionmentioning
confidence: 99%